A Comparative Study of Metabolic Syndrome Using NCEP-ATP III and IDF Criteria in Children and Its Relationship with Biochemical Indicators in Huatusco, Veracruz, Mexico - Eduardo Rivadeneyra-Domínguez; Joel Jahaziel Díaz-Vallejo; Aurora Guadalupe Prado-Bobadilla; Juan Francisco Rodríguez-Landa (MDPI AG, 2023)
Metabolic syndrome includes a set of metabolic alterations associated with overweight and obesity. The criteria for its diagnosis are heterogeneous, and there have been few studies about prevalence in the pediatric population. The aim of this study was to describe how the estimated prevalence of metabolic syndrome varies by International Diabetes Federation (IDF) vs. National Cholesterol Education Program-Adult Treatment Panel III (NCEP-ATP) criteria. We conducted a cross-sectional study in which anthropometric information, triglyceride, cholesterol, glycemia, and insulin levels, among others, were collected. We compared the group potentially misclassified by IDF with the group classified without metabolic syndrome by NCEP-ATP with respect to weight status and biomarkers. Statistical analysis included linear regression, Mann-Whitney U test, Fisher´s exact test, and odds ratio calculation. The IDF criteria missed the association with obesity, although the undetected group differed significantly from the nonmetabolic syndrome group in terms of IBM and weight. The associated biomarkers were ultrasensitive C-reactive protein (Hs-CRP), alanine aminotransferase (ALT) enzyme, insulin, triglycerides, and high-density lipoprotein (HDL) cholesterol. Waist circumference was the parameter with the strongest association for presenting metabolic syndrome, with an odds ratio of 18.33. The results of this study showed the estimated prevalence of MS varies by criteria, due to cutoff points, and how the high prevalence of MS strongly associated with obesity.